EFFECT OF INVESTMENT IN INFORMATION AND COMMUNICATION TECHNOLOGY ON FINANCIAL PERFORMANCE OF LISTED INSURANCE COMPANIES IN NIGERIA - NWALA, MAURIE NNEKA; ABUBAKAR, IDRIS AYOKANMI; ONIBIYO, EZEKIEL ROTIMI (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
Human activities have been greatly enhanced by the development of science and technology, however these innovations in Information and communication technology (ICT) come at a cost to the firm. Therefore, this study evaluates the effect of investments in ICT on financial performance of listed insurance companies in Nigeria. The population of this study is made up of 25 listed insurance companies on the Nigerian Stock Exchange from year 2012 to 2018. Insurance companies that have complete data set for the periods of 2012-2018 were selected purposively for this study, the sampled insurance companies were 16 in number. Secondary data in the form of panel data are used for this study. The data are collected from the 16 selected insurance companies annual financial reports and accounts. Based on the result of the Hausman specification test, the study adopted the Random effect regression and it revealed that Investment in ICT Hardware and software have significant positive effect on financial performance of listed insurance companies in Nigeria. The study concludes on a general note that investment in ICT improves the financial performance of listed insurance companies in Nigeria. The study therefore, recommends that listed insurance companies in Nigeria should be proactive in adoption of ICT as investments in ICT does not erode profitability.